Identification and Inventory of Lichen on Tree in the Rehabilitation Block of Sermo Kulon Progo Wildlife Reservation and Its Control in the Form of Booklets as Learning Sources - Nyawiji, Kholifah (Proceeding International Conference on Religion, Science and Education, 2022)
Lichens are one of the lower plants that rarely get attention. Thallus morphology of Lichenes. the lack of references to support learning about lichens causes the learning process to only focus on textbooks and worksheets, resulting in a lack of knowledge about lichens around them. This study aims to determine what types of lichens live on trees in the Sermo Kulon Progo Wildlife Sanctuary Rehabilitation Block, identify the results of the identification and inventory of lichens on trees in the Sermo Kulon Progo Wildlife Sanctuary Rehabilitation Block, and develop booklet identification and inventory of lichen on trees in the Sermo Kulon Progo Wildlife Sanctuary Rehabilitation Block as a learning resource. This study consisted of two stages, namely identification and inventory of lichen on trees in the Sermo Kulon Progo Wildlife Sanctuary Area Rehabilitation Block using exploratory descriptive methods and the development stage of identification and inventory booklets of lichen on trees with the development method 4 -D. Research on the identification and inventory of lichens on trees resulted in 30 species divided into 16 families with thallus foliose, crustose, fructicose, and squamulose types. The booklet was analyzed by 1 material expert, 1 media expert, and 1 biology teacher. The limited test was conducted by 24 students of class X MIPA SMAN 2 Banguntapan Bantul. Product quality assessment data was obtained from sheets in the form of a questionnaire. The results of the material expert assessment are included in the appropriate category with an average percentage of 83%, the assessment from media experts is included in the appropriate category with an assessment percentage of 80%, the assessment by the biology teacher is included in the very feasible category with an average percentage of 94%, and student assessments obtained an average percentage of 86.45% which indicates a very decent category. Based on this assessment, it can be concluded that the booklet is suitable to be used as a learning resource.